2016
DOI: 10.1097/pas.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Pure Apocrine Carcinomas Represent a Clinicopathologically Distinct Androgen Receptor–Positive Subset of Triple-Negative Breast Cancers

Abstract: Apocrine carcinomas comprise ∼1% of all breast cancers and are characterized by large cells bearing abundant eosinophilic granular cytoplasm, round nuclei, and prominent nucleoli. They are typically estrogen receptor/progesterone receptor/HER2 negative, making them unresponsive to typical hormonal or HER2-based chemotherapy. However, this subtype of triple-negative breast cancers expresses androgen receptor (AR), a feature not shared by most nonapocrine triple-negative cancers (NA-TNCs). AR therefore represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 25 publications
8
46
0
Order By: Relevance
“…Most of these findings were consistent with previous studies. Mills et al found that patients with AC more often present in older women with lower grade and T stage, which is consistent with our findings. According to two retrospective studies, the proportion of lymph node metastasis was significantly lower in patients with AC than in patients with IDC, while our results showed no difference in N stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of these findings were consistent with previous studies. Mills et al found that patients with AC more often present in older women with lower grade and T stage, which is consistent with our findings. According to two retrospective studies, the proportion of lymph node metastasis was significantly lower in patients with AC than in patients with IDC, while our results showed no difference in N stage.…”
Section: Discussionsupporting
confidence: 93%
“…An observational study of 46 breast cancer patients showed that AC was more often present in older women with lower grade and T stage compared with TNBC, but some AC patients in this study were non-TNBC. 8 Meattini et al showed that TNAC had a favorable overall survival (OS) outcome when compared with other TNBC tumors. 9 However, this study provided limited information on the prognosis for TNAC due to its small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Pure apocrine carcinoma is relatively rare accounting for <1% of primary invasive breast tumours 4. It has been defined according to strict morphological and IHC criteria by Vranic et al 3.…”
Section: Pure Apocrine Carcinoma and ‘Apocrine-like’ Invasive Carcinomamentioning
confidence: 99%
“…Since AR and androgens increase the proliferation of a molecular apocrine breast cancer cell line, MDA-MB-453, it is widely perceived, albeit falsely, that AR is an unfavorable therapeutic target and prognostic marker in molecular apocrine subtype [33,34]. However, a study compared 20 molecular apocrine cancers with 26 non-apocrine cancers for AR expression and other clinical features [35]. All apocrine carcinomas were AR-positive, while all non-apocrine tumors were AR-negative.…”
Section: Prognostic Value Of the Ar In Breast Cancermentioning
confidence: 99%